Analysis of the relationship between the increase of fuel with prices of basic needs in DKI Jakarta - Swastika Putri Puspita Madani; Chiesa Krisnaya Vendra; Michael Fumar; Muhamad Andi Nurdiansyah; Dita Ayu Saphira; Ayu Nuril Hikmah; Naufal Aulia Akbar; Ergy Bimoyoan Ermanto Nurdin Hamzah; Muhammad Daffa Fawwaz (Priviet Social Sciences Journal, 2021)
The policy of increasing fuel prices has occurred several times from time to time during the leadership at that time. The reciprocal relationship between rising production costs and declining people's purchasing power has weakened the overall economic cycle in Indonesia. In carrying out life, people in their daily lives certainly cannot be separated from basic necessities and can be said to depend on the fulfillment of these basic needs. This is indeed natural because in life, people need to consume food that comes from basic needs to meet nutritional intake. Based on the Pearson correlation value in the correlation test, it is known that the correlation value is 0.844, so the level of relationship between the increase in fuel prices and the price of basic necessities is in a very strong position.